Linguistic analysis of legal terminology in English and Uzbek (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article explores the linguistic features of legal terminology in English and Uzbek, focusing on their structural, semantic, and functional characteristics. Legal language, being a specialized form of communication, demonstrates unique lexical and syntactic properties shaped by cultural, historical, and legal traditions of each language community. The study compares the formation of legal terms, their usage in legal discourse, and the challenges of translation between English and Uzbek. Special attention is given to the analysis of polysemy, synonymy, borrowings, and the influence of Latin in English legal terms versus Arabic-Persian elements in Uzbek legal terminology. The findings highlight both commonalities and distinctions in the conceptualization and expression of legal notions, contributing to better understanding in legal translation, comparative linguistics, and legal education.